2007
DOI: 10.1186/1471-2199-8-70
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing of human peroxisome proliferator-activated receptor delta (PPARdelta):effects on translation efficiency and trans-activation ability

Abstract: Background: Peroxisome proliferator-activated receptor delta (PPARδ) is a member of the nuclear receptor superfamily. Numerous studies have aimed at unravelling the physiological role of PPARδ as a transcriptional regulator whereas the regulation of PPARδ gene expression has been less studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…This is important in view of several studies showing that the composition and length of the splice variants influence efficiency of transcription processing and halflife of the protein. 21 MK-5108 is a novel ATP-competitive inhibitor of Aurora-A. This compound showed robust selectivity against other members of the family (Aurora-B: 220 fold and Aurora C:190 fold).…”
Section: Discussionmentioning
confidence: 99%
“…This is important in view of several studies showing that the composition and length of the splice variants influence efficiency of transcription processing and halflife of the protein. 21 MK-5108 is a novel ATP-competitive inhibitor of Aurora-A. This compound showed robust selectivity against other members of the family (Aurora-B: 220 fold and Aurora C:190 fold).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for the direct activation of PPARδ by RA is controversial, with later studies suggesting that RA does not directly bind to PPARδ or activate PPAR target genes [15][17]. Nevertheless, there may well be interactions between RAR and PPARδ signalling pathways in development; for example, it has recently been suggested that neural differentiation is regulated by an RAR-mediated commitment phase followed by the promotion of differentiation via a PPARδ-mediated up-regulation of PDK1 [18]. The role of PPARδ in cell signalling is likely to be complex; five different mRNA isoforms of PPARδ have been described, with PPARδ1 and PPARδ2 being the most abundantly expressed in human tissues; although PPARδ2 has been suggested to represent an inhibitory isoform, a translational product has yet to be identified [18].…”
Section: Introductionmentioning
confidence: 99%
“…PPAR␥ is the only PPAR that has two distinct full-length translated isoforms . However, several splice variants, including truncated dominant-negative isoforms, have been detected for the three PPARs, the physiological roles of these splice variants need to be further elucidated Palmer et al, 1998;Gervois et al, 1999;Chew et al, 2003;Sabatino et al, 2005;Kim et al, 2006;Lundell et al, 2007).…”
Section: Peroxisome Proliferator-activated Receptor Familymentioning
confidence: 99%